Learning by making: exploring possibilities for a local construction ecosystem through a makerspace in Kangiqsualujjuaq - Edmonds, Isaac (Laurentian University of Sudbury, 2021)
The current construction industry in Nunavik is largely disconnected from the northern communities where the buildings themselves are constructed. Fabrication occurs in Quebec, materials are shipped north via barge and assembly is completed by a visiting southern construction crew. Furthermore, the high cost of housing in combination with rapid population growth has resulted in an ongoing housing supply crisis. Through the expansion of opportunities for local training and innovation, there lies the potential to simultaneously address several of these issues. Spaces for learning by making are an integral aspect to this effort. Inuit are their own makers and they actively continue to exercise these skills. However, vernacular design traditions have historically been ignored for the most part by southern decision makers with an institutional view of what qualifies as accepted building knowledge. This thesis addresses the question: how can the design of a makerspace serve as a means to expand local opportunities for a more sustainable, culturally reflective building ecosystem in Kangiqsualujjuaq? Review of literature on the current building delivery system and possibilities for sustainable solutions, case studies on makerspaces in northern location and an investigation of local material culture form the primary methodology. The comprehensive design of a makerspace is presented that draws inspiration from Inuit making culture with the intent to explore alternative, locally-driven avenues in the sustainable development of Kangiqsualujjuaq’s built environment. Lastly, the conclusion reflects on ways to return this work to the community and considers the wider applicability of this makerspace concept across Nunavik. Master of Architecture (M.Arch)